Pemanfaatan Teknologi Arduino untuk Deteksi Api (Fire Detector) - Ervan Asri; Yance Sonatha; Indri Rahmayuni; Andres Saputra (Ikatan Ahli Informatika Indonesia, 2018)
This fire detection system provides a fire early warning. This system works using both fire sensor and temperature sensor that is connected to Arduino UNO and Ethernet shield as a link to the internet network. All data obtained by the sensor will be saved in the database. If the data obtained by the sensor reaches a predetermined condition there will be a notification in the form of the system location and notification in the form of text messages to the user smartphone application. Aside from being a notification, the application on the smartphone user can monitor the value obtained by each sensor along with the time